Review of the genus Eupholidoptera (Orthoptera, Tettigoniidae): different genitalia, uniform song - Ciplak, Battal; Heller, Klaus-Gerhard; Willemse, Fer (Zootaxa, 2009)
The bush cricket genus Eupholidoptera, distributed across the northern Mediterranean Basin from Southern France to Israel, is reviewed. An illustrated key for males is presented. Two new species are described: Eupholidoptera helina Çiplak sp. n. and Eupholidoptera kykladica Heller & Fer Willemse & Luc Willemse sp. n.. Four species are synonymised: Eupholidoptera raggei Salman with Eupholidoptera marashensis Salman, Eupholidoptera karatolosi Mofidi-Neyestanak & Quicke and Eupholidoptera kinzelbachi Harz with Eupholidoptera megastyla (Ramme) and Eupholidoptera mirzayani Mofidi-Neyestanak & Quicke is synonymised with Apholidoptera kurda (Uvarov). Based on the male genitalia two large species groups can be distinguished within Eupholidoptera: the Eupholidoptera chabrieri group with 20 species and the Eupholidoptera prasina group with 26 species. Data relating to the male calling song of 25 species are presented. Contrary to other genera of Pholidopterini male calling songs in Eupholidoptera are relatively invariable and consist of series of isolated syllables. Since morphology is variable and the calling songs are rather invariable, radiation within the genus is the result of divergence in genitalia.